Family support for management of hypertension - Kurnia, Vera; Pauzi, Muhammad; Gusmiati, Rita; Wahyuni, Sri (Jurnal Kesehatan - STIKes Prima Nusantara, 2024)
Background: The phenomenon that occurs in hypertension patients in the internal medicine room at Dr. Achmad Darwis Suliki Hospital is that the family is not involved in managing hypertension management because the family does not know about hypertension management.Purpose: The research purpose is to examine the relationship between family support and hypertension management at homeMethods: This research uses a quantitative type with a descriptive correlation and design using a cross-sectional approach. Data collection started from October to February 2022 in the internal medicine room at Dr. Achmad Darwis Suliki Hospital with a sample of 67 respondents using an accidental sampling technique. The data collection tool used a questionnaire and was analyzed using the chi-square test.Results: The results of the study that there was a relationship between family support and hypertension management at home (p = 0.000 and OR = 18.889), with an Odds Ratio value of 18.889 so that respondents whose families supported hypertension management had 18.9 times the chance of carrying out hypertension management well.Conclusion: The family has an important role in hypertension management, family support is a motivation for sufferers to carry out hypertension management well. Health workers are expected to always educate families of hypertension sufferers so that they are involved and play an active role in carrying out hypertension management at home so that they can control blood pressure and preventive measures for the occurrence of complications in hypertension sufferers.